Mcdonald Diagnostic Criteria for Pediatric MS - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Hospital for Sick Children, University of Toronto and other centers in Canada used serial clinical and MRI examinations performed over a minimum of 24 months to retrospectively evaluate the 2010 and 2005 McDonald criteria for the diagnosis of pediatric multiple sclerosis (MS).